RICHARDS-KLUTE EQUATION’S SOLUTION STABILITY - Kolesnykov, V.A.; Lyashko, S.I. (Reports of the National Academy of Sciences of Ukraine, 2024)
The stability results of the Richards-Klute equation’s solution under perturbations of initial and boundary conditions are provided. The purpose of the article is to establish a priori estimates of the solution’s variation resulting from perturbations in the initial and boundary conditions. The primary finding demonstrates the boundedness of the solution’s variation by a linear function of the variation in the initial and boundary conditions. The case of a nonhomogeneous porous medium is also examined.